(untitled) - Schaff, Philip, 1819-1893; Schaff, David S. (Grand Rapids, MI Eerdmans, 1907)
Contents : v. V : The Middle Ages from Gregory VII, 1049, to Boniface VIII, 1294
First published in 7 volumes, 1882-1892. 8 volume set
Keywords: Church history -- the Middle Agest -- 1049 - 1294 A.D.